Modification of Calcite Properties by Mechanical Activation - Peter Baláž; Andrea Aláčová (Acta Montanistica Slovaca, 2004)
This work presents the results of changes of CaCO3 properties for zinc sorption from ZnSO4 solution and effect of mechanical activation on the sorption. The mechanical activation was performed in a planetary mill Pulverisette 6 (Fritch, Germany). Specific surface area, amorphization, and scanning electron spectroscopy (SEM) have been studied. The initial concentration of zinc solution was 25mgl-1 and pH value was 2. The influence of pH value and working temperature was also observed. The experimental results proved that mechanical activation exert an influence on changes of specific surface area and amorphization of calcite. The mechanical activation has a positive influence on the rate and effect of zinc solution. 88% of zinc sorption was determined for the sample mechanically activated 60 minutes. Calcite is an effective sorbent for Zn removal from water solutions.